Clínica psicopedagógica: uma leitura winnicottiana do sintoma escolar - Dietschi, Laiz Terezinha (2010)
This work presents a view of the learning disability symptom according to the psychoanalytical perspective of D. W. Winnicott as a sign of hope and creativity of children immersed in this kind of suffering. By presenting a clinical case, we aim at reading significant moments of the sessions, as we understand they are fundamental issues that allowed a way out of the situation where playing and learning pleasure could not arise